(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objectives: The aim of this study was done to evaluate the efficacy of beta-tri-calcium phosphate and platelet-rich fibrin on alveolar ridge for socket preservation after tooth extraction radiographically. subjects and methods: Forty patients with permanent tooth indicated for extraction divided into four groups. Group I: (The control group) socket will leave heal spontaneously, Group II: Sockets will fill with beta-tricalcium phosphate alone, Group III: Sockets will fill with PRF alone, Group IV: Sockets will fill with beta-tricalacium phosphate and PRF. The patients were evaluated for pain, swelling, infection, bone height, width, and density. Results: the lowest decrease in bone width is combination group followed by Beta-TCP group followed by PRF. there was increase in bone density in each group and more in the combination group and decrease bone loss in compare with control group. Conclusion: The use of Beta-TCP with PRF was effective in socket preservation, reduces the need for future ridge augmentation to obtain optimal, functional, and esthetic results.